The influence of accounting knowledge, auditing knowledge and ability to solve problems on the considerations of audit committee members - Wirna Listiani (Indonesia Auditing Research Journal, 2023)
The aim of this study was to examine the influence of accounting knowledge, auditing knowledge and problem-solving skills on the considerations of audit committee members. Accounting knowledge for each member of the audit committee in this study was measured through eleven questions related to the field of accounting. Audit knowledge is measured by six questions related to various aspects in the field of auditing. The ability to solve problems is measured by five questions related to the ability to solve practical problems. Meanwhile, the consideration of audit committee members is measured by providing case questions regarding differences of opinion between management and external auditors regarding revenue recognition accounting policies. This study used a research questionnaire using a Likert scale. Based on the results of the regression analysis, it shows that accounting knowledge, auditing knowledge and ability to solve problems are positively related to audit committee members. Simultaneously accounting knowledge, auditing knowledge and ability to solve problems have a significant effect on the quality of judgment of audit committee members. Partially, auditing knowledge and problem-solving skills have a significant effect on the quality of judgment of audit committee members. In contrast, accounting knowledge has no significant effect on the quality of judgment of audit committee members.